Relations between motor skills and language skills in toddlers and preschool-aged children - Elin Reikerås; Thomas Moser; Finn Egil Tønnessen (Journal for Research in Arts and Sports Education, 2021)
The purpose of this longitudinal study is to (1) examine the relations between language and motorlife skills in toddlers and preschool-aged children (n = 646) in real-life situations; and (2) to explore how the level of motor-life skills in toddlers (2 years and 9 months, T1) is related to language skills at preschool age (4 years and 9 months, T2). Data were collected through structured observation during play and daily life activities (authentic assessment) by staff in Norwegian Early Childhood Education and Care institutions. The correlations between motor-life skills and language skills at T1 were significant but small (r = .12 to .29) and were somewhat stronger at T2 (r = .18 to .46). The correlation between motor-life skills at T1 and language skills at T2 (total score) was small (rho = .25) but significant. However, the subgroups with weak and strong motor-life skills at T1 differed significantly in language skills at T2 (effect size: .40). These findings support and complement previous research, which indicates significant relations between the level of motor-life skills in toddler age and language skills in preschool age.